PHOTOELECTRIC PHOTOMETRY OF FAINT BLUE STARS AT HIGH GALACTIC LATITUDES - IRIARTE ERRO, B (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1970)
Observations of 33 blue stars at high galactic latitudes in UBV with the 40-inch telescope in Tonantzintla are presented. Most of the observed objects are main sequence stars belonging to the young galactic disk population and to the horizontal branch of
BOL OBS TONAN TACUB
Keywords: PHOTOELECTRIC, PHOTOMETRY, FAINT BLUE, STARS, GALACTIC LATITUDES; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS